Spatial gene expression profile of Wnt-signaling components in the murine enteric nervous system - Scharr, Melanie; Hirt, Bernhard; Neckel, Peter H. (Frontiers in Immunology, 2024)
Wnt-signaling is a key regulator of stem cell homeostasis, extensively studied in the intestinal crypt and other metazoan tissues. Yet, there is hardly any data available on the presence of Wnt-signaling components in the adult enteric nervous system (ENS) in vivo. Therefore, we employed RNAscope HiPlex-assay, a novel and more sensitive in situ hybridization technology. By amplifying target-specific signals, this technique enables the detection of low abundance, tightly regulated RNA content as is the case for Wnt-signaling components. Our descriptive analysis shows that several components of the multidimensional regulatory network of the Wnt-signaling pathway are present in the murine ENS. The transport and secretion protein for Wnt-ligands Wntless as well as canonical (Wnt3a and Wnt2b) and non-canonical Wnt-ligands (Wnt5a, Wnt7a, Wnt8b and Wnt11) are detectable within submucosal and myenteric plexus. Further, corresponding Frizzled receptors (Fzd1, Fzd3, Fzd6, and Fzd7) and regulatory signaling mediators like R-Spondin/DKK ligands are present in the ENS of the small and large intestine. Additionally, we compared our data to previously published physiological single cell RNA and RiboTag-based RNA sequencing analyses of enteric gliosis using data-mining approaches. Our results suggest, that canonical and non-canonical Wnt-signaling has a much broader impact on the mature ENS and its cellular homeostasis in health and inflammation, than previously anticipated.